2020
DOI: 10.1111/jph.12968
|View full text |Cite
|
Sign up to set email alerts
|

Integrating a chemical fungicide and Bacillus subtilis BIOUFLA2 ensures leaf protection and reduces ear rot (Fusarium verticillioides) and fumonisin content in maize

Abstract: Fungicides in maize production under tropical conditions reduce losses from foliar diseases, but only a few reduce ear rot incidence or mycotoxin contamination in kernels. Biocontrol agents (BCAs) may reduce postharvest losses but their efficacy has not been demonstrated in field conditions. Here, we evaluated the use of bacterial isolates in tandem with fungicides on Fusarium verticillioides incidence and fumonisin content. After an early screening, Bacillus subtilis and Streptomyces araujoniae isolates were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
(57 reference statements)
0
14
0
Order By: Relevance
“…were potential biological agents for the control of Fusarium head blight (FHB). Guimaraes et al (2020) [44] evaluated the use of bioagents (B. subtilis + Streptomyces araujoniae), in combination with fungicides (cyproconazole + azoxystrobin), on the incidence of Fusarium verticillioides in maize crop. These authors found that spraying bioagents separately from fungicides was less efficient in controlling diseases than combination spraying.…”
Section: Discussionmentioning
confidence: 99%
“…were potential biological agents for the control of Fusarium head blight (FHB). Guimaraes et al (2020) [44] evaluated the use of bioagents (B. subtilis + Streptomyces araujoniae), in combination with fungicides (cyproconazole + azoxystrobin), on the incidence of Fusarium verticillioides in maize crop. These authors found that spraying bioagents separately from fungicides was less efficient in controlling diseases than combination spraying.…”
Section: Discussionmentioning
confidence: 99%
“…applied on leaves can colonize the plant and reach the pods or seed issues 8,41,42 . Then, BBP foliar treatments may protect the grains by reducing pathogenic fungi or even mycotoxin content 23 …”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis of this work is that BBP alternated or combined with compatible chemical fungicides would better control multiple soybean diseases than conventional fungicide programs. Furthermore, beneficial bacteria can colonize the plant issues and establish positive feedbacks with the plant for a long time, protecting the commercial parts even after harvest 22,23 . The application of BBP by foliar sprays may assure the protective activities of bacterial agents against plant diseases during pre‐ and post‐harvest stages 24,25 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations